Analysis of the financial components of the functioning of professional football clubs of Ukraine - Волік [Sergey Volik], Сергій Вікторович (Slobozhanskyi Herald of Science and Sport, 2013)
This paper presents an analysis available to the public in the financial business of Premier League football clubs of Ukraine. The calculations (the «FORBES» rating, TOP-10) ranking of Ukrainian football clubs at the beginning of the championship 2013–2014 Defined the elements of financial activity of Premier League football clubs of Ukraine and main profit commands that are present in each of them. Is a rating of the visiting fans stadiums in Europe and Ukraine and income from broadcasts of football matches. Analyzed the transfer of players in the Premier League and the cost of Premier League football clubs of Ukraine. Determined that most football clubs in the Premier League is not a profitable that affects their effective functioning.